Review of how we should define (and measure) adherence in studies examining older adults' participation in exercise classes - C Todd; H Hawley-Hague; M Horne; D A Skelton (BMJ Open)
Exercise classes provide a range of benefits to older adults, reducing risk of illness, promoting functional ability and improving well-being. However, to be effective and achieve long-term outcomes, exercise needs to be maintained. Adherence is poor and reporting of adherence differs considerably between studies.Objective To explore how adherence to exercise classes for older people is defined in the literature and devise a definition for pooling data on adherence in future studies.Design Methodological review of the approaches used to measure adherence.Methods A review of the literature was carried out using narrative synthesis, based on systematic searches of MEDLINE, EMBASE, CINAHL and PsychINFO. 2 investigators identified eligible studies and extracted data independently.Results 37 papers including 34 studies were identified. 7 papers (7 studies) defined adherence as completion (retention). 30 papers (27 studies) identified adherence using attendance records. 12 papers (11 studies) based adherence on duration of exercise and 5 papers (4 studies) specified the intensity with which participants should exercise. Several studies used multiple methods.Conclusions There was little consensus between studies on how adherence should be defined, and even when studies used the same conceptual measure, they measured the concept using different approaches and/or had different cut-off points. Adherence related to health outcomes requires multiple measurements, for example, attendance, duration and intensity. It is important that future studies consider the outcome of the intervention when considering their definition of adherence, and we recommend a series of definitions for future use.